The influence of acute stress exposure on cognitive reappraisal: a psychophysiological study - Michèle Wessa; Magdalena Sandner; Jérôme Rimpel; Sandra Schönfelder (Stress, 2024)
AbstractSuccessful and efficient emotion regulation (ER) is a key mechanism for mental health. However, acute stress may impact the ability to cognitively regulate negative emotions due to its immediate effects on executive functioning. Based on previous studies, we expected that the time at which ER is tested after a stressor might have a decisive influence, with impairments in ER being more pronounced immediately after stress as compared to a later post-stress phase. To investigate such a time-dependent effect of stress on ER, we investigated 50 healthy adults (26 female) who were exposed to either the Trier Social Stress Test (n = 25) or a control condition (n = 25). Afterwards subjects conducted a cognitive ER task during which they were instructed to either regulate (cognitive reappraisal) or passively view neutral and negative visual stimuli. The ER task was divided into an early (0–20 minutes) and a late post-stress phase (20–40 minutes). Salivary cortisol and α-amylase were assessed as markers of the neuroendocrine stress response. Self-reported emotional state, the mean activity of the late positive potential measured via electroencephalogram (EEG), and corrugator electromyographic activity (EMG) were used as indices of ER. While the groups did not differ in the early post-stress phase, our results suggest a stress-related impairment in ER in the late post-stress phase. This effect was evident in all ER outcome variables (subjective rating, EEG, and EMG data). These results suggest a time-specific stress effect on cognitive reappraisal, which would have implications for reappraisal as a possible stress management technique.